Model of Fostering Student Tolerance in The Process of Learning a Foreign Language - Allamuratov Gofur Ashurovich (Genius Publishing Group, 2022)
Nowadays, a lot of attention is paid to teaching children foreign languages. Particular emphasis is placed on English, German, Spanish and French, which have become the world's languages. This article focuses on cultivating tolerance in foreign language learning and illustrating their models.
Keywords: Tolerance; Reforms; Models; Education System